ПОЗААУДИТОРНА РОБОТА ЯК ВИХОВНИЙ ЗАСІБ ПРОФЕСІЙНОЇ ОСВІТИ (Педагогіка вищої та середньої школи, 2008)
The attempt to define components of system of extracurricular pedagogical work as an educational mean of professional education is made in this article.